A scoping review of roof harvested rainwater usage in urban agriculture: Australia and Kenya in focus. (20th November 2018) - Amos, Caleb Christian; Rahman, Ataur; Karim, Fazlul; Gathenya, John Mwangi
Abstract: This review investigates the potential of using roof harvested rainwater to support urban agriculture. Among the important issues, we concentrate on system configuration, modelling and economic analysis while comparing research from both developed and developing countries. Urban agriculture contributes notably to food and nutrition in many developing nations, and is receiving increasing attention in developed countries due to a cultural shift towards sustainable living coupled with increasing demand and food prices. Domestic rainwater harvesting (RWH) from rooftops increasingly forms part of integrated water management strategies and has seen a considerable amount of research on modelling and economics, as has water use in agriculture. However domestic RWH usually focuses on in-house usage such as toilet flushing and washing, while there has been very little research specific to its use in food production. In developing countries home gardens often fail due to insufficient rainfall and water supply. In general, promoting urban agriculture and the greening of cities begs the question of whether there is sufficient water available to support it and where additional water will come from. A scoping review following a five step criteria is adopted here to understand the extent to which roof harvested rainwater can be used to support urban agriculture and what are the associated economic implications. In view of the broad scope of the water-food-energy-ecosystem nexus, under which this research fits, this scoping review is deemed better suited (in absence of an ample body of literature) to the synthesis of relevant researches than a systematic review. The major contributions of this review are to highlight the lack of initiatives to utilise harvested rainwater in urban agriculture, to explore the obstacles and to lay a foundation for new areas of research within the sustainable urban development paradigm. Furthermore, the comparison between developed and developing countries helps bring to light cultural, socio-economic and political obstacles to improving sustainability and healthier living in the urban environment. The impact of history and traditions on crop choice, growing methods and consequently water consumption rates are also discussed. This review is particularly relevant to three of the United Nations' Sustainable Development Goals (i.e. Cleaner and Sustainable Cities; Health and Wellbeing and No Hunger). It is found that there is a considerable potential to supply water to urban agriculture using customised roof RWH system designs. For example, one study reports that up to 41% of urban horticulture sites in Rome could be sustained by water harvested from local roofs. Irrigating a small garden (20 m 2 ) with harvested rainwater can increase the yield by about 20% meeting the caloric requirements of a typical Indian household. Further research is needed on the integration of roof rainwater harvesting and urban agriculture to maximise its contribution to food production and sustainability. Highlights: There is little research on roof harvested rainwater use in urban agriculture. Modelling and economic analysis of RWH and urban agriculture systems reviewed. The integration of RWH with urban agriculture is an important future research area.